Phosphorus doped and defect modified graphitic carbon nitride for boosting photocatalytic hydrogen production. Issue 1 (7th December 2022) - Chen, Lu; Yan, Guiyang; Liu, Xiyao; Ying, Shaoming; Xia, Yuzhou; Ning, Shangbo; Wang, Xuxu
Abstract : The PCN x photocatalyst exhibits a remarkable photocatalytic hydrogen production rate of 59.1 μmol h −1, which was 123.1 times higher than that of pristine g-C3 N4 . Its apparent quantum efficiency was 8.73% at 420 nm. Abstract : The enhancement of photogenerated carrier separation efficiency is a significant factor in the improvement of photocatalyst performance in photocatalytic hydrogen evolution. Heteroatom doping and defect construction have been considered valid methods to boost the photocatalytic activity of graphitic carbon nitride. Herein, we report graphitic carbon nitride modified with P doping and N defects (PCN x ), and the effects of doping and defects were investigated in photocatalytic H2 evolution. Its hydrogen evolution rate can reach up to about 59.1 μmol h −1, which is more than 123.1 times higher than pristine graphitic carbon nitride under visible light irradiation. Importantly, the apparent quantum efficiency reaches 8.73% at 420 nm. The excellent performance of the PCN x photocatalyst was attributed to the following aspects: (I) the large BET surface area of PCN x affords more active sites for H2 production and (II) the introduction of P and N defects can accelerate the charge carrier separation and transfer efficiency, leading to more efficient photocatalytic hydrogen production. The photocatalyst showed obviously enhanced activities.